AB0755 Urticarial vasculitis: A clinical and histopathologic review. (23rd January 2014) - Loricera, J.; Calvo-Río, V.; Ortiz-Sanjuán, F.; González-Lόpez, M.; Fernández-Llaca, H.; Rueda-Gotor, J.; González-Vela, M.; Mata-Arnáiz, C.; Peña-Sagredo, J.; González-Gay, M.; Blanco, R.
Abstract : Background: Urticarial vasculitis is an infrecuent subset of vasculitis described by McDuffy et al, in 1973, characterized clinically by urticarial skin lesions of more than 24 hours duration and histologically by vasculitis. Objectives: Our aim was to evaluate the frequency, clinical and pathological features and treatment of UV from a large series of patients with cutaneous vasculitis. Methods: Retrospective study of UV from a serie of 565 patients with cutaneous vasculitis of a University Hospital. For the diagnosis of UV, besides urticarial lesions persisting more than 24 hours, a skin biopsy showing necrotizing vasculitis of small vessels was required. Results: UV was observed in 11 (1.95%) of 565 patients with cutaneous vasculitis. There were 4 men and 7 women, with a mean age of 52.18±19.39 years (range, 14 to 78 years). Precipitating factors and/or possible causes identified were upper respiratory tract infection (1 case), drugs (amoxicillin, 1 case) and a malignancy (megakaryocytic leukemia, 1 case). In addition to urticarial lesions, other features such as palpable purpura (5 patients), arthralgias (5 patients), arthritis (2 patients), abdominal pain (2 patients), and nephropathy (2 patients) were observed. Hypocomplementemia (low C4) was observed in only 1 of the 11 patients. Other Abnormal laboratory data observed were increase of ESR (5 cases), leukocytosis (3 cases), anemia (2 cases), positive ANA (1 case), and positive Rheumatoid Factor (1 case). Neither of the patients with positive ANA or Rheumatoid Factor developed systemic lupus erythematosus, rheumatoid arthritis or any other connective-tissue disease. The main histological findings were vascular and perivascular infiltration, endothelial swelling and fibrinoid necrosis. The cellular infiltrate was composed mainly of neutrophils, lymphocytes and eosinophils. The most common treatments were corticosteroids (6 cases), antihistaminic drugs (4 cases), chloroquine (4 cases), colchicine (2 cases), NSAIDs (1 case). Cytotoxic agents were not required in any of the patients. After a mean follow-up of 13±12 months (median 11 months) recurrences were observed in 4 patients. A patient died because of an underlying malignancy while the remaining had full recovery without complications. Conclusions: UV is a rare subtype of cutaneous vasculitis. In addition to urticarial skin lesions, joint involvement was the most common clinical manifestation. Corticosteroids and antihistaminic drugs are the drugs more commonly used. The prognosis depends on the underlying disease but is usually good. References: McDuffie FD, Sams WM, Malddonado JE, Andreini PH, Conn DL, Samayoa EA. Hypocomplementemia with cutaneous vasculitis and arthritis. Possible immune complex syndrome. Mayo Clin Proc 1973; 48:340-348, Disclosure of Interest: None Declared